Effect of Garlic Extract on Lactic Culture - Singh, S.P.; Kumar, Shashikant; Kumar, Birendra (Asian Journal of Chemistry, 2010)
In the present notes the aim is to determine the effect of different garlic extract concentrations on the acid producing activity of L.bulgaricus and L. delbrueckii.